(untitled) (Damascus University Journal of agriculture sciences, 2021)
Four concentrations of aqueous extract of dried leaves of Melia azedarach were tested in vitro to determine their effect on egg hatch and second stage juveniles mortality of Meloidogyne. incognita. These result were compared with nemakic 30 and non-treated control. Egg hatch was completely inhibited and juveniles’ Mortality was 100% in the nematicide treatment, while hatching was 29.28- 40.71- 57.87- 69.58- 98.415 when concentrations of (100-80-60-40%) and non treated were applied, respectively. juveniles’ Mortality was 32-53.33 -72 -77.33 -9% at the same treatments. There was no significant difference in Mortality between (80 and 100%) concentrations, while differences were significant in the other treatments.